The high mountains of portugal ebook A novel. - Martel, Yann (2016)
NEW YORK TIMES BESTSELLER • “Fifteen years after The Life of Pi, Yann Martel is taking us on another long journey. Fans of his Man Booker Prize–winning novel will recognize familiar themes from that seafaring phenomenon, but the itinerary in this imaginative new book is entirely fresh. . . . Martel’s writing has never been more charming.”—Ron Charles, The Washington Post NAMED ONE OF THE BEST BOOKS OF THE YEAR BY NPR In Lisbon in 1904, a young man named Tomás discovers an old journal. It hints at the existence of an extraordinary artifact that—if he can find it—would redefine history. Traveling in one of Europe’s earliest automobiles, he sets out in search of this strange treasure. Thirty-five years later, a Portuguese pathologist devoted to the murder mysteries of Agatha Christie finds himself at the center of a mystery of his own and drawn into the consequences of Tomás’s quest. Fifty years on, a Canadian senator takes refuge in his ancestral village in northern Portugal, grieving the loss of his beloved wife. But he arrives with an unusual companion: a chimpanzee. And there the century-old quest will come to an unexpected conclusion. The High Mountains of Portugal —part quest, part ghost story, part contemporary fable—offers a haunting exploration of great love and great loss. Filled with tenderness, humor, and endless surprise, it takes the reader on a road trip through Portugal in the last century—and through the human soul. Praise for The High Mountains of Portugal “Just as ambitious, just as clever, just as existential and spiritual [as Life of Pi ] . . . a book that rewards your attention . . . an excellent book club choice.” — San Francisco Chronicle “There’s no denying the simple pleasures to be had in The High Mountains of Portugal .” — Chicago Tribune “Charming . . . Most Martellian is the boundless capacity for parable. . . . Martel knows his strengths: passages about the chimpanzee and his owner brim irresistibly with affection and attentiveness.” — The New Yorker “A rich and rewarding experience . . . [Martel] spins his magic thread of hope and despair, comedy and pathos.” — USA Today “I took away indelible images from High Mountains, enchanting and disturbing at the same time. . . . As whimsical as Martel’s magic realism can be, grief informs every step of the book’s three journeys. In the course of the novel we burrow ever further into the heart of an ape, pure and threatening at once, our precursor, ourselves.” —NPR “Refreshing, surprising and filled with sparkling moments of humor and insight.” — The Dallas Morning News “We’re fortunate to have brilliant writers using their fiction to meditate on a paradox we need urgently to consider—the unbridgeable gap and the unbreakable bond between human and animal, our impossible self-alienation from our world.” —Ursula K. Le Guin, The Guardian “[Martel packs] his inventive novel with beguiling ideas. What connects an inept curator to a haunted pathologist to a smitten politician across more than seventy-five years is the author’s ability to conjure up something uncanny at the end.” — The Boston Globe “A fine home, and story, in which to find oneself.” —Minneapolis Star Tribune